The Heroes of Olympus : The House of Hades - Book 4 - Riordan, Rick (New York : Disney/Hyperion Books, 2013)
"Greek and Roman demigods from the Prophecy of Seven must work together to seal the Doors of Death--and help Percy and Annabeth escape the Underworld in the process"--
Keywords: Jackson, Percy (Fictitious character) -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Giants -- Juvenile fiction; Camps -- Juvenile fiction; Hera (Greek deity) -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Jackson, Percy (Fictitious character) -- Fiction; Mythology, Roman -- Fiction; Mythology, Greek -- Fiction; Giants -- Fiction; Camps -- Fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Legends, Myths, Fables / Greek & Roman